Systematic epidemiological studies to identify and resolve health constraints to smallholder dairy production in coastal lowland Kenya - Maloo, S.H.; Thorpe, W.R.; Ngumi, P.N.; Perry, Brian D. (1994)
Since 1989, a step-wise series of farming systems surveys and epidemiological studies have been carried out in coastal Kenya to identify and resolve major disease constraints affecting smallholder dairy production. This paper describes the sequential studies and reports on the significance of, and intervention against, East Coast fever (ECF). The study was carried out in Kaloleni Division which has three agro-ecological zones (AEZ). In the point-prevalence study, exposure to ECF 20, measured by detection of antibodies to T. Parva schizonts in the indirect fluorescent antibody test, was influenced by AEZ and grazing system. In the wetter areas T. Parva antibody prevalence in free grazing cattle was higher than in drier area while in the wetter zero-grazed dairy cattle had a lower prevalence than those in the free-grazing system.